Integrated Population Genomic Analysis and Numerical Simulation to Estimate Larval Dispersal of Acanthaster cf. solaris Between Ogasawara and Other Japanese Regions - Horoiwa, Mizuki; Nakamura, Takashi; Yuasa, Hideaki; Kajitani, Rei; Ameda, Yosuke; Sasaki, Tetsuro; Taninaka, Hiroki; Kikuchi, Taisei; Yamakita, Takehisa; Toyoda, Atsushi; Itoh, Takehiko; Yasuda, Nina (Frontiers in Marine Science, 2022)
The estimation of larval dispersal of marine species occurring on an ecological timescale is significant for conservation. In 2018, a semi-population outbreak of crown of thorns starfish, Acanthaster cf. solaris was observed on a relatively isolated oceanic island, Ogasawara. The aim of this study was to assess whether this population outbreak was caused by large-scale larval recruitment (termed secondary outbreak) from the Kuroshio region. We estimated larval dispersal of the coral predator A. cf. solaris between the Kuroshio and Ogasawara regions using both population genomic analysis and oceanographic dispersal simulation. Population genomic analysis revealed overall genetically homogenized patterns among Ogasawara and other Japanese populations, suggesting that the origin of the populations in the two regions is the same. In contrast, a simulation of 26-year oceanographic dispersal indicated that larvae are mostly self-seeded in Ogasawara populations and have difficulty reaching Ogasawara from the Kuroshio region within one generation. However, a connectivity matrix produced by the larval dispersal simulation assuming a Markov chain indicated gradual larval dispersal migration from the Kuroshio region to Ogasawara in a stepping-stone manner over multiple years. These results suggest that, while large-scale larval dispersal from an outbreak of the Kuroshio population spreading to the Ogasawara population within one generation is unlikely. This study also highlighted the importance of using both genomic and oceanographic methods to estimate larval dispersal, which provides significant insight into larval dispersal that occurs on ecological and evolutionary timescales.